Pengaruh terapi Modalitas : Senam lansia Terhadap Depresi Pada Lansia di Panti Sosial Lansia Harapan Kita Palembang - Ridwan; Indra Febriani (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2021)
Background One of the therapeutic uses of the Elderly Gym Modality is used for someone who has depression, the results may be different if the elderly are actively involved in a specially designed series of exercise activities. Gradually elderly sadness are resolved through developing happy experiences. the effectiveness of elderly gymnastics therapy as a therapeutic tool will occur if the therapist has sufficient skills to make exercise the right tool. The purpose of this study was to determine the effect of therapy modalities: elderly exercise on depression in the elderly at the Harapan Kita Social Home for the Elderly in Palembang in 2020. This research method is a Quasi-Experimental research with the design used is a